Hubungan Kualitas Tidur Dengan Gejala Depresi Pada Penderita Stroke : Literature Review - Rifka Novita Sari; Refki Sanjaya Pratama; Dini Nur Alpiah (JURNAL ILMIAH NUSANTARA, 2024)
The influence of poor sleep quality will cause physical activity to be hampered. The National Institutes of Health recommends that to maintain a healthy condition, individuals should sleep 7-8 hours per day. Namn Hidayat (2013) explained that the need for sleep depends on the level of development and society, exercise for health and relaxation is useful for increasing body strength and bringing the body to optimal condition (Asmadi, 2008). Post-stroke patients also experience psychological disorders, this is due to the inability to carry out daily activities as usual to prevent emotional instability in patients and a decrease in quality of life after a stroke. Depression can also improve the functional, physical, psychological and social conditions of stroke patients who have begun to deteriorate, as well as the high recovery rate of stroke patients who do not experience depression. The aim of this study was to understand the relationship between quality of life, depression and stroke patients. The research used the Literature Review method, carried out using the PICO search in the Google Scholar database. There were 5 journals that met the criteria and showed results that there was a relationship between sleep quality and depression symptoms in stroke sufferers